Entre as tiranias holandesas e o tirano governador: governação na capitania de Pernambuco (1645-1646) (Revista de História da UEG (REVHIST), 2019)
In the year of 1645, a group of residents of Pernambuco proclaimed the War of Divine Freedom against the rule and dominion of the Dutch West India Company. Before the Portuguese Crown, the participants of the movement argued that they rebelled because of the innumerable and constant tyrannies to which they were submitted by the dutch authorities. A few months later, however, a series of complaints were made in the portuguese Court accusing the governor of the war, João Fernandes Vieira, of committing excesses and tyrannies in the government of Pernambuco. Thus, this work aims to analyze the use of a juridical-political argument present in the Portuguese political cultures of the seventeenth-century, tyranny as a justification for the dismissal of rulers, by the various groups of residents in the captaincy of Pernambuco to achieve their political objectives